A new deep-sea species of Vemana J.L. Barnard, 1964 (Amphipoda, Amphilochidea, Vemanidae) from off southern Gulf of Mexico - Ortiz, M.; Winfield, I. (Zootaxa, 2022)
Vemanidae Lowry & Myers, 2017, is an amphipod family restricted to the world’s deep waters, with four benthic species inhabiting both bathyal and abyssal zones from the Caribbean Sea, South California, and the Mozambique Channel. During an oceanographic campaign carried out in the southern Gulf of Mexico, a single male specimen of a new species of Vemana J.L. Barnard, 1964 was collected from the deep-sea soft bottom, which is described in detail herein. The new species mainly differs from those four Vemana species by coxa 4 posteroventral corner prolonged forming an acute tooth, basis posterior margin of pereopod 7 with 6 evident teeth, antenna 1 flagellar article 1 lower margin with callynophore, and first urosome segment convex with a diminutive hump. The new species is morphologically closest to Vemana lizata Barnard, 1964, which was collected from the Caribbean Sea at 4077 m depth. Besides, a dichotomous key for the identification of the 5 known Vemana species worldwide is provided.